Governance and Choice of Upper Secondary Education in the Nordic Countries Access and Fairness - Rasmussen, Annette; Dovemark, Marianne (Cham : Springer International Publishing : Imprint: Springer, 2022)
This work discusses how the complex relationship between welfare policies of equity and market efficiencies/deficiencies of education policies is handled in local practices. It offers contributions from the five Nordic countries - Norway, Sweden, Denmark, Finland and Iceland - and pays special attention to questions about access and diversity in upper secondary education. The book draws on a wide range of theoretical frameworks and research projects and provides multiple perspectives of how upper secondary staff and students have experienced reforms of education governance during the last two or three decades. The research projects range from in-depth case studies to the analysis of large-scale data sets and inform practitioners, policy makers and researchers about practices of education policy that are highly influenced by market forces.
Chapter 1. Education in the Nordic Countries: Governance and Choice -- Part 1. Access and Governance -- Chapter 2. Governing Students' Access to Knowledge: A Critical Discourse Analysis of General Subjects in the Swedish Upper Secondary School Reforms between 1990 and 2011 -- Chapter 3. Social Inclusion and Equality in Access: Comparing Vocational Education in Sweden and Denmark -- Chapter 4. Governing School Choice in Norway - Why Local Educational Government Capacity Matters -- Chapter 5. Upper-Secondary School Choices in Reykjavík and Helsinki: The Selected Few in the Urban -- Part 2. Segregation and Fairness -- Chapter 6. The Janus Face of 'Freedom of Choice' in Upper-Secondary School Markets -- Chapter 7. Revisiting Just Education for Students Last in Line - a Norwegian Perspective -- Chapter 8. Choice and Competition in the Governance of the Danish Gymnasium School -- Chapter 9. "It is not all about studying". General Upper Secondary Schools' Institutional Habitus Shaping Students' Educational Choice Making -- Chapter 10. Selection for Whom? Upper Secondary School Choice in the Light of Social Justice -- Chapter 11. Comparing Governance and Choice of Upper Secondary School in the Nordic Countries.
Keywords: Schools; Education and state; Educational sociology; School and Schooling; Educational Policy and Politics; Sociology of Education